Luce Irigaray and premodern culture : thresholds of history - Krier, Theresa M., 1953-; Harvey, Elizabeth D. (Routledge studies in Renaissance literature and culture, 2004)
This volume explores the pre-Enlightenment roots of Luce Irigaray's thought and the impact of her writings on our understanding of classical, medieval, and Renaissance culture.